An ecological viewpoint on the variations of water temperature, salinity, conductivity, pH and dissolved oxygen during a 45-minute tidal outflow at a small tropical estuary - Yap, Chee Kong (2009)
The study of ecology includes how a living organism interacts with its surrounding which includes living (biotic) and nonliving (abiotic) components. KTBatu ofPahang is a pristine recreational rocky shore (Figure 1), located in the east coast of Peninsular Malaysia (Figure 2). Therefore, this allows study on the natural variation of physico-chemical parameters more effective with minimal anthropogenic impact.